AUTHORITY OF THE CLERGY: SOCIO-THEOLOGICAL REFLECTIONS - Kundukulam, Vincent (Asian Horizons, 2021)
Authority is a form of power attached to individuals on account of the social positions they own in the society. The fact that the ordinary men do not have sufficient measures to verify whether authorities exercise power with proper mandate gives chance to authorities to employ far more power than what is attached to their office. Priesthood is a unique profession with high potential to use authority thanks to the sacred nature attached to it. The interplay between the variety of means at their disposal to render security to those who are in ontological uncertainty and their natural crave for social attraction provide them with plenty of opportunities to misuse power. The misuse of clerical authority can be controlled by a gospel-oriented vision of life. In this regard, a revised perspective of authority is indeed necessary. According to the mind of Jesus, who reduced Himself to the status of a slave, authority consists in diakonia. In difference to the gentile praxis, He founded authority on the Beatitudes. From an ecclesiological perspective, authority is a gift received from God for the realization of His salvific plan for the whole world. Hierarchy does not possess any autonomous status apart from the people of God. Hierarchy is placed in the position of command to structure the responsibility which is common to all. As the unity of Trinity arises from the communion of three persons in God, the unity of ecclesial community is maintained through the communion among its members. Clerical authority is the special call addressed to some members in the Church in order to build up the Body of Christ in love, truth and justice through a witnessing life. It necessitates a shift from essentialist to existentialist concept of priesthood according to which the priest will be like a co-traveller and primary reference in matters of faith.